P577 Associations between penile-anal intercourse and oral sex and viral STIs in the united states, 2011–2015. (14th July 2019) - Habel, Melissa; Leichliter, Jami; Dittus, Patricia; Spicknall, Ian; Aral, Sevgi
Abstract : Background: Anal and oral sex are related to the acquisition and transmission of STIs, and condom use remains low for these behaviors. Thus, we examined associations between these behaviors and STIs using 2011–2015 National Survey of Family Growth data. Methods: We examined associations between male-female penile anal intercourse (PAI) and oral sex with opposite-sex partners only (lifetime) and lifetime self-report of a viral STI (herpes or genital warts) by sex and race/Hispanic origin (White, Hispanic, Black, Other). The response rate was 71.0% and sensitive survey items were asked using audio computer-assisted self-interview. Analyses were restricted to individuals reporting one lifetime sex partner. Bivariate analyses were analyzed in SUDAAN-11.0 using chi-squares. Results: Overall, more women (12.5%, N=11, 243) than men (2.1%, N=9, 257) reported ever having a viral STI. Self-report of viral STI was slightly more common among White women compared to women of other racial/ethnic groups. Among women, ever engaging in PAI was strongly associated with a viral STI diagnosis (21.8%[SE 1.2] White, 20.7%[SE 2.0] Black, 19.7%[SE 3.2] Other, and 16.9%[SE 1.7] Hispanic, p<0.0001) as was giving/receiving oral sex (all 11.6%–17.3%). For men, the same associations differed by race/Hispanic origin. PAI was significantly associated with a viral STI in White men (5.7%[SE 0.7], p<0.01), Hispanic men (3.4%[SE 1.0], p<0.05), and men of other racial/ethnic groups (2.7%[SE 1.2], p<0.05). Oral sex was associated with a viral STI in White men and men of other racial/ethnic groups; however, for Black men only giving oral sex was significantly associated with a viral STI (4.1%[SE 1.0], p<0.05). Conclusion: For women, PAI and oral sex were related to having been diagnosed with a viral STI. Self-reported viral STIs were highest in women and Whites which may suggest disparities in health care seeking and access. Further exploration is needed to assess associations between multiple sex partners and condom use during these behaviors. Disclosure: No significant relationships.